A Critical Review on The Job Creation Omnibus Law-Forming Process - Bobi Yusuf Noor Fajar; Zaid Zaid (Syiah Kuala Law Journal, 2021)
This study aims to conduct a critical study of the process of formulating the "omnibus law" on job creation from the perspective of legal politics and good governance through a normative method using a conceptual and statute approach and utilizing secondary and primary legal materials which are then critically analyzed through prescription. The results of this study ultimately conclude that from a legal political perspective, the process of forming this law is very problematic and procedurally flawed. In addition, this law is a response from policymakers who are political in nature to a complex situation which in fact creates complex derivative problems as well. This is inseparable from the nature of the omnibus law itself, which lacks democracy, participation, reduces accuracy and prudence in its preparation, and has the potential to exceed the provisions in the constitution. Therefore, based on the good governance point of view, the process of forming the Omnibus Law on Job Creation has not fulfilled the principles of good governance in the form of the principles of legitimacy, transparency, accountability, responsiveness, and the rule of law. The principles of effectiveness and efficiency in the principles of good governance in this Law can still be considered